Improving The Methodological Training Of Primary School Teachers On The Basis Of An Integrated Approach - Barno Abdullaeva,Azizbek Toshkhonov (International Journal of Advanced Science and Technology, 2020)
This article discusses the content of the structural components of the integrative approach of training of primary school teachers. The integrative approach makes it possible to solve a number of issues of intensification and efficiency in the professional training system of primary school teachers, the solution of which by other means is very difficult. It is important to understand that the possibility of such a wide application of the integrative approach in the case under study is determined by the specifics of the professional activity of the primary school teacher in all its main manifestations should be based on the idea of ​​integration, but with the necessary elements of differentiation, which should still be subordinate.